Measurement of intelligence in teenagers and adults by method of application: traditional and computerized - Gamarra T., Christiam (2012)
Initially we applied the Raven intelligence test to a group of 240 subjects, among adolescent’s students and adults,university employees (teachers and tutors of courses), after this first evaluation we selected 120 subjects whose scores are homogeneous direct (mean equal to 29, whereas those whose minimum score is 27and maximum of 31). In this second group intelligence test applied "Toni 2," half of them the traditional way with pencil and paper test form, the rest was applied to the computerized version, designed in Excel 2010 (for the design of the computerized version took into account the fact of not leaving any details aside from the original test, whose change was the application instructions). Comparing the overall results found that computerized assessment group got more than half compared to the group that developed the test in the traditional way; this difference was not manifested in their initial test results. Similarly we find that the adolescent group the difference is even greater, significant differences in the difference of their means with regard to the mode of application, in the adult group there is no significant difference. Another interesting research found is that the scores of validity and reliability of items of evidence are different in both groups. Overall scores are higher reliability in the computerized version, with the difference highlighted in the adolescent group (a higher rate of reliability).